Priority issues for women, health and development in Thailand : a resource book for strategic planning and policy-making - Ambhorn Meesook (National Committee on Women, Health and the Environment, National Commission on Women's Affairs, 1995)
Papers presented at the National Seminar on Women, Health, and Development at Bangkok on August 18, 1994.